REPRESENTASI BAHASA DALAM PERTARUNGAN SIMBOLIK DAN KEKUASAAN - Winarsih, Suko (Pusat Pengembangan Bahasa IAIN Tulungagung, 2013)
The relation representation between power and harassment in the globalization era does not only appear concretely involving physical activities. Both operate in the representation of the symbol force to create the truth. Through representation, the reality is represented in the form of symbol system mobilisation such as language or discourse, pictures, and the like. The truth representation through symbolic universality produces social mechanism, which relates between power and harassment. The representation which should contain harmony between the tokens and something represented in some cases makes the reality vague. This is happened because the symbolic system as the medium is dominated by the certain power system.